Simulation of Plume Patterns Associated with Different Atmospheric Temperature Profiles - Reza Sahebnasagh, Mohammad; Esfahanian, Vahid; Gitipour, Saeid; Ahmadi, Goodarz; Ashrafi, Khosro (Asian Journal of Chemistry, 2010)
Computational fluid dynamics (CFD) has been used to study the effects of wind velocity and temperature profiles on the patterns of the pollutant dispersion by using the Fluent CFD code for three cases of atmospheric stability conditions. The discrete phase model (DPM) along with Reynolds stress turbulence model (RSM) was used to model the dispersion pattern. For neutrally stable atmospheric condition, the velocity, temperature, turbulence kinetic energy (TKE) and dissipation profiles predicted by the model in downwind direction were compared with the results of other investigators to assess the accuracy of the model. It was observed from the simulation results that the pollutant dispersion and turbulence intensity patterns strongly depend on the temperature profile. In addition, the TKE profile was shown to be a good indicator of the mixing zone and the dispersion patterns. These results can be used to assess environment impact of coastal industries which are under various diurnal temperature profiles.